Clinical and microbiological profile of urinary tract infection in children less than five years of age - N, Madhu G; S, Harish; Sharanappa, Siva (Indian Journal of Child Health, 2018)
Background: Urinary tract infection (UTI) is a common bacterial illness of pediatric age group. UTIs, especially in young children, have non-specific signs and symptoms that can be undetected or misdiagnosed. Delaying diagnosis and treatment of UTIs may result in long-term renal complications. Objectives: The objectives were to study the clinical presentation of UTI, common uropathogens, and antimicrobial sensitivity pattern among children